2010
DOI: 10.1111/j.1537-2995.2009.02412.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved plasma removal efficiency for therapeutic plasma exchange using a new apheresis platform

Abstract: The SPO has improved performance characteristics over the CSP. Based on our results, the SPO is acceptable for use in therapeutic plasma exchange programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
51
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 14 publications
14
51
3
Order By: Relevance
“…The superior efficacy of the Spectra Optia TPE protocol over the COBE Spectra system has previously been demonstrated in a nonblinded, randomized, crossover comparative clinical study [2]. The positive results were confirmed later in several single arm usability studies with a total of >150 procedures.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…The superior efficacy of the Spectra Optia TPE protocol over the COBE Spectra system has previously been demonstrated in a nonblinded, randomized, crossover comparative clinical study [2]. The positive results were confirmed later in several single arm usability studies with a total of >150 procedures.…”
mentioning
confidence: 76%
“…Dual needle continous flow has inherently higher average inlet flow rates than single needle intermittent and therefore shorter procedure times. The double needle procedure may however not solely explain the more rapid TPE procedure with Spectra Optia, as the Optia system was also proven to be faster than COBE Spectra [2,3]. A shorter procedure time is particularly appreciable for chronically ill patients who will spend less time per procedure, and for young and working patients who report an increase in quality of life [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Moreover, Tormey et al have demonstrated higher plasma removal efficiency for Optia in comparison to the Cobe. 16 At first, we did not consider increased plasma efficiency when the devices were switched for SPD procedures. Rather than focusing on inlet flow, the Optia SPD software can be conveniently programmed to cap the plasma pump flow rate automatically, if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…More modern systems now have continuous control over the interface in a continuously flowing system. This reduces cellular loss and maximizes the efficiency of plasma removal [16]. Double-filtration plasmapheresis [17] aims to reduce the loss of the lower molecular weight molecules otherwise lost in the filtration process, returning them to the patient.…”
Section: Method: Centrifugation or Filtration?mentioning
confidence: 99%